Subtle Matters of Theory and Emphasis: Richard Lee and Controversies about Foraging Peoples - Patterson, Thomas C. (Anthropologica, 2022)
From the late 1960s onward, two divergent views about human nature came to dominate studies of kin-communal societies. One derives from the liberal views of John Locke (not Thomas Hobbes); the other builds on Rousseau's critique of the liberal contract theorists and incorporates the views of Lewis Henry Morgan, Karl Marx, and Frederick Engels. In the 1970s, the former was associated with the work of Sherwood Washburn and Napoleon Chagnon among others; the latter with the writings of Richard Lee, Eleanor B. Leacock, and Janet Siskind. This paper examines the differences between the two viewpoints; it shows how this dichotomy underpinned subsequent debates about the peoples of the Kalahari.